A precipitation-hardened high-entropy alloy with outstanding tensile properties. (1st January 2016) - He, J.Y.; Wang, H.; Huang, H.L.; Xu, X.D.; Chen, M.W.; Wu, Y.; Liu, X.J.; Nieh, T.G.; An, K.; Lu, Z.P.
Abstract: Recent studies indicated that high-entropy alloys (HEAs) possess unusual structural and thermal features, which could greatly affect dislocation motion and contribute to the mechanical performance, however, a HEA matrix alone is insufficiently strong for engineering applications and other strengthening mechanisms are urgently needed to be incorporated. In this work, we demonstrate the possibility to precipitate nanosized coherent reinforcing phase, i.e., L12 -Ni3 (Ti, Al), in a fcc-FeCoNiCr HEA matrix using minor additions of Ti and Al. Through thermomechanical processing and microstructure controlling, extraordinary balanced tensile properties at room temperature were achieved, which is due to a well combination of various hardening mechanisms, particularly precipitation hardening. The applicability and validity of the conventional strengthening theories are also discussed. The current work is a successful demonstration of using integrated strengthening approaches to manipulate the properties of fcc-HEA systems, and the resulting findings are important not only for understanding the strengthening mechanisms of metallic materials in general, but also for the future development of high-performance HEAs for industrial applications. Graphical abstract: Through controlled thermomechanical processes and microstructure, extraordinary balanced tensile properties at room temperature were achieved via formation of a high density of nanosized coherent reinforcing phase, i.e., L12 –Ni3 (Ti, Al), in a fcc-FeCoNiCr high-entropy alloy matrix.